2019
DOI: 10.1101/643221
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide RNAi screen for context-dependent tumor suppressors identified using in vivo models for neoplasia in Drosophila

Abstract: Genetic approaches in Drosophila have successfully identified many genes involved in regulation of growth control as well as genetic interactions relevant to the initiation and progression of cancer in vivo. Here, we report on large-scale RNAi-based screens to identify potential tumor suppressor genes that interact with known cancer-drivers: The Epidermal Growth Factor Receptor and the Hippo pathway transcriptional cofactor Yorkie. These screens were designed to identify genes whose depletion drove tissue expr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Thus, all experimental crosses had one copy of GFP, while control crosses had two copies of GFP. Detailed methodology is provided in Groth et al (2020) . Larval images were taken in bright field and in GFP channel with a Leica stereomicroscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, all experimental crosses had one copy of GFP, while control crosses had two copies of GFP. Detailed methodology is provided in Groth et al (2020) . Larval images were taken in bright field and in GFP channel with a Leica stereomicroscope.…”
Section: Methodsmentioning
confidence: 99%
“…We have reported an in vivo screen in Drosophila ( Groth et al 2020 ), wherein we have identified a large number of genes, which, when depleted, enhanced growth induced by Yki and EGFR. More importantly, these genes function like classical tumor suppressors as, when downregulated in the background of overexpressed Yki or EGFR, we observed neoplastic growth.…”
mentioning
confidence: 99%
“…The resulting giant larva phenotype can be used in genetic screens to identify tumor causing genotypes. We made use of this property to identify candidate genes in a genetic screen for tumor suppressors cooperating with Yki (the entire screen is published elsewhere [9]). We found that RNAimediated depletion of bin3 and Hexim, components of the 7SK snRNA complex in combination with Yki overexpression led to massive overgrowth in wing disc tissue and giant larval phenotype (Fig.1B).…”
Section: Depletion 7sk Snrnp Complex Components Cooperates With Yki Imentioning
confidence: 99%
“…Thus, our observations suggest that, Drosophila 7SK snRNP complex may function to repress tumorigenic potential of Yki in vivo in an epithelial tumor model. It was intriguing to find multiple components of the two spatio-temporally separated protein complexes, involved in regulation of transcription elongation, among the tumor suppressors identified in a genome wide screen for factors cooperating with Yki in growth regulation [9].…”
Section: Depletion 7sk Snrnp Complex Components Cooperates With Yki Imentioning
confidence: 99%
See 1 more Smart Citation